Treatment of acute cervical internal carotid artery dissection using the Solitaire FR revascularization device. (7th January 2013) - To, Chiu Yuen; Badr, Yaser; Richards, Boyd
Abstract : During treatment of a right internal carotid artery terminus aneurysm, an acute iatrogenic flow limiting dissection was caused in the cervical internal carotid. The true lumen was catheterized using a Mirage 0.008 microwire over an Excelsior SL-10 microcatheter, which was exchanged for a Marksman microcatheter. A 6 mm×30 mm Solitaire FR revascularization device was then deployed across the dissection as a salvage technique.